Challenges and Opportunities of Online Higher Education during the COVID- 19 Pandemic in Romania – a Framework for Sustainable Education - Paștiu, Carmen; Maican, Silvia; Muntean, Andreea (<center>Conference Proceedings Determinants Of Regional Development</center>; No 3 (2022): Conference Proceedings - IX International Scientific Conference Determinants of Regional Development, 2022)
This study focuses on challenges and opportunities of online teaching in Romania as the key factors in adapting education to digital age for accomplishing one of the sustainable development goals of the European Commission. An online survey was used as a quantitative method of data collection, and data were collected through an online questionnaire from a sample of Romanian university teachers. The research questions concerned the following topics: 1) How was the preparation for online teaching organised before pandemic period; 2) What challenges related to emergency remote teaching were faced in 2020; 3) What are the actual challenges (2021) and future perspectives of online teaching; 4) What digital infrastructures and tools for teaching were used. The findings reflect that the most frequent challenges faced were related to students’ engagement and with ICT infrastructure. These results support the importance of how the emergent disruptions caused by the COVID-19 pandemic could be used as an opportunity to reshape the role of online teaching for Education in Digital Age.